(untitled) (New Yersey, 2002)
Book is collection of document in Proceedings of the Workshop Contemporary Geometry and Related Topics was held in Belgrade, Yugoslavia, 15-21 May 2002
Keywords: Hình học topo,Geometry, Modern,Topology,Hình học, hiện đại